Isolation, characterization, and gene expression analysis of Wharton’s jelly-derived mesenchymal stem cells under xeno-free culture conditions - Venugopal P (Dove Medical Press, 2011)
Parvathy Venugopal1, Sudha Balasubramanian1, Anish Sen Majumdar1, Malancha Ta21Stempeutics Research Pvt. Ltd, Manipal Hospital, Bangalore, India; 2Manipal Institute of Regenerative Medicine, Manipal University, Bangalore, IndiaAbstract: Mesenchymal stem cells (MSCs) have become an attractive tool for tissue engineering and targets in clinical transplantation due to their regeneration potential and immuno-suppressive capacity. Although MSCs derived from bone marrow are the most widely used, their harvest requires an invasive procedure. The umbilical cord, which is discarded at birth, can provide an inexhaustible source of stem cells for therapy. The Wharton’s jelly-derived MSCs (WJ-MSCs), from the umbilical cord, have been shown to have faster proliferation rates and greater expansion capability compared with adult MSCs. The standard isolation and in vitro culture protocol for WJ-MSCs utilizes fetal bovine serum (FBS) or calf serum as a nutrient supplement. However, FBS raises potential safety concerns such as transmission of viral/prion disease and may initiate xenogeneic immune reactions against bovine antigens. Therefore, for therapeutic applications, there is an urgent requirement to establish an alternative nutrient supplement which would favor cell proliferation, retain MSC characteristics, and prove safe in human subjects. In the present study, we isolated and expanded WJ-MSCs in 5% pooled, allogeneic human serum (HS) supplemented with 2 ng/mL of basic fibroblast growth factor. For cell dissociation, porcine trypsin was replaced with TrypLE, a recombinant enzyme, and a protease-free protocol was adapted for isolation of MSCs from WJ. We determined their growth kinetics, in vitro differentiation potential, surface marker expression, and colony-forming unit potential and compared them against standard WJ-MSC cultures expanded in 10% FBS. All these parameters matched quite well between the two MSC populations. To test whether there is any alteration in gene expression on switching from FBS to HS, we analyzed a panel of stem cell and early lineage markers using Taqman® low density array. No significant deviation in gene expression was observed between the two populations. Thus we established an efficient, complete xeno-free protocol forpropagation of human WJ-MSCs.Keywords: human serum, explant, trypLE, umbilical cord, FBS, bFGF